Enhancement of oxygen evolution performance of water splitting at high current density by novel electrodeposited NiFe-LDH coatings (2025)
Efficient water splitting is a key goal in renewable hydrogen production. However, it is a high-demand energy process. Hence, developing highly efficient and inexpensive electrocatalysts is essential to overcoming this challenge. The cell voltage of the electrochemical water splitting is between 1.8 and 2 V, much higher than the theoretical minimum value of 1.23 V, being the oxygen evolution reaction (OER), the most kinetics limiting process, having overpotentials between 210–330 mV at a current density of 30 mA cm-2. This work develops low-cost and scalable electrodes for OER by electrodeposition of NiFe layered double hydroxide (LDH) coatings, with different Ni:Fe ratios in the electrodeposition bath. Coating obtained with Ni:Fe ratio of 15:1 exhibits the best catalytic activity for OER and shows the lowest Tafel slope of 38.5 mVdec-1 and the lowest overpotentials of only 206 and 244 in 1 M NaOH at 30 and 100 mAcm-2, respectively, which are the most favorable kinetics parameters respect to those found in literature reports. Furthermore, this developed coating material shows excellent electrocatalytic stability for OER after 80 h of operation at a high current density of 400 mAcm-2 in an alkaline medium, which is a typical condition for practical operation of electrolyzers. The developed catalytic coating by electrodeposition technique shows high performance and stability, economical and straightforward reproducibility. It also supports conformational coatings on complex three-dimensional and high-surface-area substrates, like nickel foam, making it a highly scalable process.